OFR-33(2)-79 Application Of A Total System Surface Mine Simulator To Coal Stripping - Volume II - User's Manual For A Surface Mining - Materials Handling Simulator - C. B. Manula (The National Institute for Occupational Safety and Health (NIOSH), 1976)
This report is mainly concerned with the modification and development of a users manual for the Open-Pit Materials Handling Simulator (OPMHS) developed at Penn State. Model Modifications included the introduction of a free-format input, the application of a Weibull random generator, facilities to stochastically simulate shovel-dragline operations, and routines to increase the flexibility in making truck assignments. At the same time, core storage requirements and execution times were minimized and all P.S.U. conventions were removed to allow operation on other computing systems.